Organizational Commitment and Intention to Leave of Nurses in Portuguese Hospitals - Neves, Teresa (2022)
Intention to leave is influenced by the commitment and individual and structural factors. It is a critical dimension in health systems due to the shortage of professionals and the potential impact on the quality of care. The present paper: (i) characterizes organizational commitment and intention to leave; (ii) analyzes the relationship between structural factors (such as, work environment and nurse staffing), individual factors (age), and nurses' organizational commitments and intention to leave; and (iii) analyzes the differences in the intention to leave and in the organizational commitment according to service specialty, nurses' specialization, and contractual relationship in Portuguese public hospitals. A cross-sectional study was conducted with a sample of 850 nurses from 12 public hospitals units. The results show a high affective and continuance commitment of nurses with the hospital, and a reduced tendency of the intention to leave. A significant positive association was also found between the intent to leave and individual/structural factors. Organizational commitment and intention to leave levels are satisfactory, despite the influence of several factors, such as nurse staffing, work environment, or other opportunities for professional development. The results identify particularly sensitive areas that, through adequate health and management policies, can reduce nurses' intentions to leave and promote the sustainability of the health system.